2018
DOI: 10.3390/md16100358
|View full text |Cite
|
Sign up to set email alerts
|

Peniginsengins B–E, New Farnesylcyclohexenones from the Deep Sea-Derived Fungus Penicillium sp. YPGA11

Abstract: Chemical examination of the EtOAc extract of the deep sea-derived fungus Penicillium sp. YPGA11 resulted in the isolation of four new farnesylcyclohexenones, peniginsengins B–E (1–4), and a known analog peniginsengin A (5). The structures of compounds 1–4 were determined on the basis of comprehensive analyses of the nuclear magnetic resonance (NMR) and mass spectroscopy (MS) data, and the absolute configurations of 1, 2, and 4 were determined by comparisons of experimental electronic circular dichroism (ECD) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The remaining acetyl group was located at C-14 (C 71.3) by the HMBC correlation from H2-14 to the acetyl carbonyl carbon (C 172.9). The strong NOESY correlations of H3-13/H2-5, H2-8/H-6, H3-15/H2-9, and H2-14/H-10 indicated that both Δ 6 and Δ 10 had an E configuration. The specific rotation of 1 ([] 20 D 0) indicated that 1 was racemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining acetyl group was located at C-14 (C 71.3) by the HMBC correlation from H2-14 to the acetyl carbonyl carbon (C 172.9). The strong NOESY correlations of H3-13/H2-5, H2-8/H-6, H3-15/H2-9, and H2-14/H-10 indicated that both Δ 6 and Δ 10 had an E configuration. The specific rotation of 1 ([] 20 D 0) indicated that 1 was racemic.…”
Section: Resultsmentioning
confidence: 99%
“…Some possess unique carbon skeletons and some exhibit remarkable bioactivities such as enzyme inhibition, antitumor activity, and antiviral activity. As part of our ongoing efforts to discover bioactive molecules from marine-derived fungi [9][10][11], chemical examination of a deep-sea sediment-derived Aspergillus terreus YPGA10 led to the isolation of a carotane-type sesquiterpene aspterric acid (3) and two new biogenetically related sesquiterpenes (1 and 2). Herein, the isolation and structural identification were described.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical study of the extract of deep-sea fungus Penicillium sp. YPGA11 [ 327 ] led to the isolation of four new antibacterial meroterpenoids farnesylcyclohexenones, peniginsengins B–E ( 503 – 506 ), that contained rare motifs for natural compounds, i.e., 1‑methylcyclohexene cycle and (4 E ,8 E )-4,8-dimethyldeca-4,8-dienoic acid.…”
Section: Compounds Of Mixed and Unidentified Originmentioning
confidence: 99%
“…In our efforts to search for new or bioactive molecules from deep-sea-derived Penicillium or Aspergillus strains [12][13][14][15], chemical examination of Penicillium thomii YPGA3 afforded a new austalide meroterpenoid (1) and seven known analogues (2−8) ( Figure 1). Compound 1 represented the third example of austalides bearing a phenol hydroxy at C-5 instead of the conserved methoxy in other known analogues.…”
Section: Introductionmentioning
confidence: 99%